2017
DOI: 10.1017/s1368980017002452
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, anthropometric and behavioural risk factors for ultra-processed food consumption in a sample of 2–9-year-olds in Brazil

Abstract: The present study is the first to evaluate associations between less healthy dietary patterns of Brazilian 2-9-year-olds and parental feeding practices. Our findings highlight sociodemographic, anthropometric and behavioural factors within families that could be used to target tailored policies to at-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 63 publications
7
28
0
9
Order By: Relevance
“…LBW infants whose mothers had eight years or less of schooling and did not work outside the home had lower dietary diversity. The negative association between maternal education and diet quality, characterized by high UPF consumption and low diet adequacy 27 , as well as between maternal work and inappropriate eating practices, is consistent with findings in countries in Africa, Asia and Latin America, including Brazil 28 .…”
Section: Caracteristics Of Sample N Total or Median A % By Category Osupporting
confidence: 84%
“…LBW infants whose mothers had eight years or less of schooling and did not work outside the home had lower dietary diversity. The negative association between maternal education and diet quality, characterized by high UPF consumption and low diet adequacy 27 , as well as between maternal work and inappropriate eating practices, is consistent with findings in countries in Africa, Asia and Latin America, including Brazil 28 .…”
Section: Caracteristics Of Sample N Total or Median A % By Category Osupporting
confidence: 84%
“…Together these studies support straightforward immediate effects of promoting intake, with potentially positive direct consequences for intake, depending on the food encouraged. Further, consistent with the prediction that less controlling forms of limitation should have more beneficial effects on child intake, Monitoring has been associated with lower intake of sugar‐sweetened beverages assessed via 24 h dietary recall in 5–10 year‐olds 14 and decreased consumption of foods high in fat, sugar and salt assessed via food frequency questionnaire (FFQ) among preschoolers 15,16 and school‐aged children 17 . However, a Portuguese study including 4 year‐old children reported that greater Monitoring (i.e.…”
Section: Introductionsupporting
confidence: 52%
“…Table 1 presents a summary of seven cohort studies from HHDC and MHDC [ 21 , 24 , 26 , 28 , 29 , 42 , 63 ]. Table 2 presents a summary of 19 cross-sectional or cohort studies with cross-sectional analysis from HHDC [ 20 , 23 , 27 , 40 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 53 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], and Table 3 presents a summary of 16 cross-sectional studies from MHDC [ 22 , 25 , 30 , 31 , 32 , 33 , 38 , 41 , 47 , 50 , 51 , 52 , 60 , 70 , 71 , 72 ]. The studies conducted by Borges et al [ 47 ] and by Manyanga et al [ 70 ] included HHDC, MHDC and LHDC.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three articles had a cross-sectional design [ 20 , 22 , 23 , 25 , 27 , 30 , 31 , 32 , 33 , 38 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 60 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], and seven of the remaining articles were cohorts studies [ 21 , 24 , 26 , 28 , 29 , 42 , 63 ]. Sample size ranged widely, from 232 [ 30 ] to 18,046 subjects [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation